Marketing management - Kotler, Philip; Keller, Kevin Lane , 1956- (Prentice Hall, 2012)
For undergraduate and MBA marketing management and strategy courses. Kotler/Keller is the gold standard in the marketing management discipline because it continues to reflect the latest changes in marketing theory and practice